Traffic Safety 2016
DOI: 10.1136/injuryprev-2016-042156.76
|View full text |Cite
|
Sign up to set email alerts
|

76 European facts and the global status report on road safety 2015

Abstract: BackgroundRoad traffic injuries are the leading cause of premature death in young people aged 5–29 years in the WHO European Region. The Decade of Action for Road Safety 2011–2020 was adopted by the United Nations General Assembly in 2010 to reduce the global toll of road traffic injuries by 2020.MethodsThis fact sheet describes the status of road safety in 52 out of the 53 Member States of the WHO European Region, representing 95% of the Region’s population. Experts from several sectors in each country reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Of these, the mortality rate ratio between HIC and LMIC due to road traffic injuries has increased by 2.3 times between 2000 and 2015. Unfortunately, the rapid motorisation seen with economic development in LMIC has not been complemented by adequate development of legislative and regulatory mechanisms to improve vehicular safety and road infrastructure and modify road user risk behaviours [ 24 , 25 ]. Whereas most countries in the European region have reported a decline, many LMIC have reported an increase or levelling off of road traffic mortality rates [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the mortality rate ratio between HIC and LMIC due to road traffic injuries has increased by 2.3 times between 2000 and 2015. Unfortunately, the rapid motorisation seen with economic development in LMIC has not been complemented by adequate development of legislative and regulatory mechanisms to improve vehicular safety and road infrastructure and modify road user risk behaviours [ 24 , 25 ]. Whereas most countries in the European region have reported a decline, many LMIC have reported an increase or levelling off of road traffic mortality rates [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) has estimated that injuries as a result of road accidents cost countries approximately 3% of their Gross National Product with the figure rising to 5% in some low-and middle-income countries (WHO, 2016). Countries in the WHO European region, which includes the European Union (EU) and the Commonwealth of Independent States, reported societal costs of road accidents between 0.6% and 5.8% of their Gross Domestic Product (GDP) with a median of 1.4% of the GDP (Jackisch, Sethi, Mitis, Szymañski, & Arra, 2015). In Italy, there is little evidence on the costs of road traffic injuries, but a study conducted by the Italian Institute of Statistics reported that in 2014, medical costs, production and human losses amounted to 18 billion Euros, 1.3% of the country's GDP (Istituto Nazionale di .…”
Section: Introductionmentioning
confidence: 99%
“…Impact of noise from transport causes the high level of stress, elevated blood pressure, risk of cardiovascular diseases, some types of oncology, aggravation of psychological problems. It can cause not only stress, but also development delay of children, decrease in abilities to mathematics, later skills of reading [5,6].…”
Section: Resultsmentioning
confidence: 99%